Power Management of AC/DC Hybrid Distribution Network With Multi-Port PET Considering Reliability of Power Supply System - Xu, Xinxing; Huang, Wentao; Hu, Yan; Tai, Nengling; Ji, Yaming; Xie, Ning (Frontiers in Energy Research, 2021)
In the current distribution network, photovoltaic, wind power, energy storage and other distributed energy are widely connected, and the proportion of generalized DC load is rapidly increasing. With the development of power electronics technology, using multi-port power electronic transformer (PET) to achieve high-efficiency access of large capacity AC/DC source and load is the current research hotspot, and the distribution network will form the AC/DC hybrid power supply. The introduction of a large number of power electronics and the flexible coordinated control and complementary fault-tolerant advantages of PET bring challenges to the operation and maintenance management of AC/DC hybrid power system. In this paper, the structure of AC/DC hybrid power system with multi-port PET cluster is introduced. Based on the idea of hierarchical and partitioned control, a three-layer control mode of integrated automation system, PET cluster controller and PET controller is proposed; Aiming at the problem of reliability evaluation, a sequential Monte Carlo simulation method is proposed to simulate the AC/DC hybrid power system with multi-port PET cluster. The influence of multi-port PET parallel cluster mode and port capacity limitation on the reliability of power system is analyzed, and the effectiveness of the model and algorithm is verified. Finally, an example is given to verify that the proposed structure is conducive to improving the utilization level of renewable energy in distribution network.